A critical role of striatal A2AR–mGlu5R interactions in modulating the psychomotor and drug‐seeking effects of methamphetamine. (15th May 2015) - Wright, Sherie R.; Zanos, Panos; Georgiou, Polymnia; Yoo, Ji‐Hoon; Ledent, Catherine; Hourani, Susanna M.; Kitchen, Ian; Winsky‐Sommerer, Raphaelle; Bailey, Alexis
Abstract: Addiction to psychostimulants is a major public health problem with no available treatment. Adenosine A2A receptors (A2A R) co‐localize with metabotropic glutamate 5 receptors (mGlu5 R) in the striatum and functionally interact to modulate behaviours induced by addictive substances, such as alcohol. Using genetic and pharmacological antagonism of A2A R in mice, we investigated whether A2A R–mGlu5 R interaction can regulate the locomotor, stereotypic and drug‐seeking effect of methamphetamine and cocaine, two drugs that exhibit distinct mechanism of action. Genetic deletion of A2A R, as well as combined administration of sub‐threshold doses of the selective A2A R antagonist (SCH 58261, 0.01 mg/kg, i.p.) with the mGlu5 R antagonist, 3‐((2‐methyl‐4‐thiazolyl)ethynyl)pyridine (0.01 mg/kg, i.p.), prevented methamphetamine‐ but not cocaine‐induced hyperactivity and stereotypic rearing behaviour. This drug combination also prevented methamphetamine‐rewarding effects in a conditioned‐place preference paradigm. Moreover, mGlu5 R binding was reduced in the nucleus accumbens core of A2A R knockout (KO) mice supporting an interaction between these receptors in a brain region crucial in mediating addiction processes. Chronic methamphetamine, but not cocaine administration, resulted in a significant increase in striatal mGlu5 R binding in wild‐type mice, which was absent in the A2A R KO mice. These data are in support of a critical role of striatal A2A R–mGlu5 R functional interaction in mediating the ambulatory, stereotypic and reinforcing effects of methamphetamine but not cocaine‐induced hyperlocomotion or stereotypy. The present study highlights a distinct and selective mechanistic role for this receptor interaction in regulating methamphetamine‐induced behaviours and suggests that combined antagonism of A2A R and mGlu5 R may represent a novel therapy for methamphetamine addiction. Abstract : Adenosine A2A receptors (A2A R) co‐localize and functionally interact with metabotropic glutamate 5 receptors (mGlu5 R) in the striatum. The present study demonstrates that both genetic deletion of A2A R, or co‐antagonism of A2A R and mGlu5 R, prevented methamphetamine‐ but not cocaine‐induced hyperactivity and stereotypic rearing and prevented methamphetamine‐induced reward. Chronic methamphetamine, but not cocaine, significantly increased striatal mGlu5 R binding in wild‐type, but not A2A R knockout mice. These findings suggest a functional A2A R‐mGlu5 R in the striatum to selectively regulate methamphetamine psychomotor and rewarding properties.